Galynska O. M. Nature’s cultural code in Ukrainian and English intertextual phraseologisms - Galynska O. M. (Philological Treatises, 2020)
The article focuses on the investigation of nature’s cultural code, namely, how the images of the nature are comprehended and evaluated by a human in culture during the life process. The Ukrainian and English phraseologisms serve the material for the comparative analysis of image’s and symbolic peculiarities of the nature’s components in the structure of phraseological units.